THE EFFECT OF FINANCIAL LITERACY AND POCKET MONEY ON STUDENTS' FINANCIAL MANAGEMENT BEHAVIOR THROUGH FINANCIAL SELF-EFFICACY (A STUDY OF ACTIVE FEB STUDENTS AT STATE UNIVERSITY OF MAKASSAR) - Fakhirah Husain; Adhiba Nur Fayyad; Imelda; Icha Patadungan (RADJA PUBLIKA, 2025)
This study examines the role of financial literacy and pocket money on students' financial management behavior, with financial self-efficacy as an intervening variable. The phenomenon of increasing student consumer behavior is the main background of this study. Using a quantitative explanatory approach with SEM-PLS analysis on 130 active students of the Faculty of Economics and Business, Makassar State University, the results show that financial literacy and pocket money have a positive effect on financial self-efficacy, and financial self-efficacy has a significant effect on financial management behavior. However, financial literacy does not have a direct effect without the mediation of financial self-efficacy. This means that the higher the financial literacy and pocket money accompanied by self-confidence in managing finances, the better the students' financial behavior in planning and controlling expenses wisely.